“I Need to Belong”: Examining a Negative Halo Effect for Expressions of the Need to Belong - Kevin P. McIntyre; Matthew M. Peebles; Brent A. Mattingly (Interpersona: An International Journal on Personal Relationships)
We examine a problem faced by individuals with a high need to belong; expressing a desire for social relationships may make it more difficult to form them. In particular, we suggest expressions of heightened belongingness needs create a negative halo effect whereby people expressing those needs appear to be less attractive and more desperate to potential relationship partners. In two experiments, participants viewed hypothetical targets who endorsed high, moderate, or low levels of the need to belong, and then rated these targets on measures of social attractiveness and social desperation. Results revealed that participants rated both high and low need to belong targets as low in social attractiveness (Experiment 1, N = 116) and social stature (Experiment 2, N = 111), relative to the moderate need to belong target. However, participants rated the high need to belong target significantly higher in social desperation, compared to the moderate and low need to belong targets. Lastly, social desperation significantly mediated the association between (high vs. moderate) expressed need to belong and social attractiveness, suggesting that expressing heightened need to belong is uniquely unattractive to others as it conveys a sense of social desperation. Overall, these results suggest that when they express a desire to form close relationships, those high in the need to belong may have a difficult time achieving a sense of belonging.